Healthcare Biclustering-Based Prediction on Gene Expression Dataset. - Ramkumar, M.; Basker, N.; Pradeep, D.; Prajapati, Ramesh; Yuvaraj, N.; Arshath Raja, R.; Suresh, C.; Vignesh, Rahul; Barakkath Nisha, U.; Srihari, K.; Alene, Assefa (BioMed Research International, 2022)
In this paper, we develop a healthcare biclustering model in the field of healthcare to reduce the inconveniences linked to the data clustering on gene expression. The present study uses two separate healthcare biclustering approaches to identify specific gene activity in certain environments and remove the duplication of broad gene information components. Moreover, because of its adequacy in the problem where populations of potential solutions allow exploration of a greater portion of the research area, machine learning or heuristic algorithm has become extensively used for healthcare biclustering in the field of healthcare. The study is evaluated in terms of average match score for nonoverlapping modules, overlapping modules through the influence of noise for constant bicluster and additive bicluster, and the run time. The results show that proposed FCM blustering method has higher average match score, and reduced run time proposed FCM than the existing PSO-SA and fuzzy logic healthcare biclustering methods.